Training women's pelvic floor muscles during pregnancy and postpartum at primary health centers: a best practice implementation project. Issue 3 (1st September 2021) - de Viñaspre, Regina Ruiz; Garrido, Ana Elena; Alvarez, Maria Angeles
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Introduction and aims: Pelvic floor muscle training (PFMT) enhances muscle strength and coordination, and prevents urinary incontinence associated with giving birth. The goal was to improve women's PFMT during pregnancy and postpartum in La Rioja, Spain. Methods: This evidence implementation project used the JBI evidence implementation framework. First, we conducted the PFMT baseline audit: to assess the criteria for midwife training, we sent a questionnaire to all midwives. To measure the criteria for PFMT and urinary incontinence risk assessment, we reviewed the medical records of 60 women selected through consecutive sampling and 15 other women at risk of urinary tract infections (UTIs) for the inclusion criteria in a PFMT program. Second, we used the Getting Research into Practice guidelines to identify barriers to the fulfillment of each criterion and design and implement strategies to improve compliance. Finally, we repeated the audit to measure compliance and verify the changes. Results: The midwives received updated PFMT, optimizing compliance with the first criterion from 67 to 100%. The remaining criteria – providing PFMT for pregnant women, identifying women at high risk of incontinence, and facilitating a supervised PFMT program for women at high risk of UTIs – went from 0% compliance to 17, 96, and 67%, respectively. Conclusion: This project was effective in building consensus, improving midwives' practice, and facilitating mothers' PFMT. The project continued during the novel coronavirus [coronavirus disease 2019 (COVID-19)] epidemic in Spain as the midwives, women, and managers were involved in the change because of a well designed registration system and the use of online tools for communication between midwives and women.